2020
DOI: 10.1186/s13229-020-00392-9
|View full text |Cite|
|
Sign up to set email alerts
|

Differentially altered social dominance- and cooperative-like behaviors in Shank2- and Shank3-mutant mice

Abstract: Background Recent progress in genomics has contributed to the identification of a large number of autism spectrum disorder (ASD) risk genes, many of which encode synaptic proteins. Our understanding of ASDs has advanced rapidly, partly owing to the development of numerous animal models. Extensive characterizations using a variety of behavioral batteries that analyze social behaviors have shown that a subset of engineered mice that model mutations in genes encoding Shanks, a family of excitatory postsynaptic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Notably, the increased social dominance phenotype observed in Spred1-/- mice is highly similar to increased social dominance observed in the tube test in several other mouse models for monogenic forms of ASD, including several different Shank3 mouse models [ 60 , 61 ], Shank2 Δ6−7 mice [ 62 ] and Fmr1 y/- mice [ 40 ]. Increased winning in the tube may model an inability to recognize the social status of conspecifics.…”
Section: Discussionsupporting
confidence: 62%
“…Notably, the increased social dominance phenotype observed in Spred1-/- mice is highly similar to increased social dominance observed in the tube test in several other mouse models for monogenic forms of ASD, including several different Shank3 mouse models [ 60 , 61 ], Shank2 Δ6−7 mice [ 62 ] and Fmr1 y/- mice [ 40 ]. Increased winning in the tube may model an inability to recognize the social status of conspecifics.…”
Section: Discussionsupporting
confidence: 62%
“…Cre-expression, and thus deletion of Shank3 in neocortical excitatory neurons (ex4-22|ALL-NEX Cre ), Dlx5/6 -positive GABAergic forebrain neurons (ex4-22|ALL-Dlx5/6 Cre ), which include various subclasses of neocortical interneurons but also MSNs as principal striatal projection neurons [ 169 – 174 ], DRD1- (ex4-22|ALL-Drd1 Cre ) and DRD2-positive neurons (ex4-22|ALL-Drd2 Cre ) [ 129 ], did not induce the phenotype previously observed in the constitutive KO model [ 128 ], though it has to be noted that such deficits of constitutive KO mice were also not replicated in this study. Mixed evidence and even conflicting results concerning social interaction deficits were observed in the models ex9|ANK [ 82 , 175 ], ex13|PDZ [ 139 , 176 ], ex21|PRO [ 125 , 177 179 ], and the rat model ex6|ANK [ 134 , 180 ]. Intact social motivation and interaction was described in the analysis of the models ex4-7|ANK [ 90 ], ex8|ANK-Q321R [ 132 ], ex21|PRO-InsG3728 [ 126 ], and ex11-21|SH3-PRO in rats [ 135 ].…”
Section: Main Textmentioning
confidence: 99%
“…Mixed evidence concerning the ability to recognize familiar conspecifics was observed in the model ex13-16|PDZ [ 90 , 155 , 161 , 164 , 166 , 168 ], where some studies found aberrant social recognition, while it seemed to be intact in others. No deficits of social recognition were found in the murine models ex4-9|ANK [ 78 , 80 , 167 ], ex9|ANK [ 82 , 175 ], ex14-16|PDZ [ 131 ], and ex21|PRO-InsG3728 [ 126 ]. Similarly, specific deletion of SHANK3 in dorsal telencephalic excitatory neurons and glia (ex14-16|PDZ-Emx1 Cre ) [ 133 ], or GABAergic neurons (ex14-16|PDZ-Viaat Cre ) [ 131 ] did not cause dysfunctional social recognition.…”
Section: Main Textmentioning
confidence: 99%
“…However, using house mice as subjects allows easier molecular-genetic manipulations and convenient coupling to other established behavior assays. In a recent study, Kyung et al used Shank2 KO and Shank3 KO mice to model autism spectrum disorder; they evidenced increased and decreased cooperative behaviors in Shank2 KO and Shank3 KO mice, respectively, which additionally correlated well with altered social dominance behaviors 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the performance between mice and rats in this assay, we found the efficacy (defined as the number of rewards divided by activity) in mice was only about half that in rats, which further reduced to¼ considering the mouse box is also half-long. Futhermore, the latency (defined as time to receive the first reward) in mice is one order of magnitude higher 14,15 . The low efficacy and high latency in mice make the assay insensitive for detecting subtle behavioral alterations.…”
Section: Introductionmentioning
confidence: 99%